Ograniczenia wskaźników zdrowia publicznego monitorowanych w kontekście zrównoważonego rozwoju - Mariola Zalewska (Problemy Zarządzania, 2015)
The concept of sustainable development refers to efforts to improve in a harmonious way economic, social and environmental dimensions. One of the main aspects of the social dimension of sustainable development is public health. In the introduction the role of indicator systems to monitor the effectiveness of any policy, including sustainable development is recalled. Usually such systems contain a subset of the public health indicators. This is the case Eurostat and GUS databases. In the paper a qualitative analysis of such subset of indicators available through the Eurostat database is carried out. The life expectancy is the leading indicator with a variant of the healthy life years. Quoted is the rationale for excluding this variant from analyzes that compare different populations due to subjectivity of this option. Later in the article a lack of indicators to which a visible impact on the leading indicator could be attributed is concluded. Consequently, the subset of indicators under consideration can not be treated as a decision support tool. Thus, its meaning is limited to the information and comparison purposes.